Evaluation of Physical Security of Indonesian Formed Police Units' Garuda Camp in the Perspective of Crime Prevention Through Environmental Design - Putri, Anggraini; Murimann, Chairul; Aminanto, Ezra (Technium Social Sciences Journal, 2021)
Indonesia is one of the Police Contributing Countries (PCC) in the United Nations Peacekeeping Operations. Since 1989, Indonesia has deployed their police officers into various peacekeeping missions, either individually or in the units called Formed Police Units (FPU). In deploying the FPU, Indonesia as the PCC is not only responsible for preparing the personnel, but also equipping the FPU in logistics and infrastructure, which includes appropriate camps in the mission area. These camps have an important role as the operational and administrative base of the FPU, personnels accommodation, assets storage facility, and notably as the symbol of Indonesia’s commitment to its contribution to world peace. Garuda Camp Indonesian FPU in MINUSCA, Central African Republic, was built in 2018 by the International Relations Division of The National Police with total assets more than 500 billion rupiahs. During the 2 years of placing the Indonesian FPU in MINUSCA, several security threats have occurred in this camp, such as theft and burglary. In this case, the camp security is an important element to ensure the Unit's success in performing its mission mandate. Therefore, the author sees the need for an evaluation using the perception of Crime Prevention Through Environmental Design (CPTED) to increase the level of security at Garuda Camp. This is based on CPTED which has a basic idea that proper and effective design in the use of the built environment can lead to a reduction in crime and fear of crime, as well as an improvement in the quality of life in an environment. The author explores threats and use qualitative methods to identify the compliance of physical security requirements in the camp. The result of the study shows that Garuda Camp is included in the medium level threat category. Thus, a threat prevention strategy is needed.